THREE-DIMENSIONAL MODELING OF THE SESAMOID BONES - Catal, Hatice; Corumluoglu, Ozsen (STEF92 TECHNOLOGY LTD, 2012)
In this research, digital image processing techniques was used to create 3-dimensional (3D) virtual model of sesamoid bones. As study materials, Ballerina's and sedentary women's axial MDCT (Multidetector Computed Tomography) feet images were utilized. For the determination bone boundaries in each slides, image preprocessing and then segmentation steps were followed. All these processing steps was done in 3D-Doctor software. All the measurements were obtained over the 3D model formed. Various statistical ratios were computed regarding the area, volume and length measurements. The comparison done in the study was performed by using these ratios for sedentary and ballerinas. As an outcome, some differences were found in sesamoid bones of ballerina and sedentary women.
Keywords: Segmentation; Image Processing; Ballerina; MDCT; 3D Model; Geology; Mining & Mineral Processing